2015
DOI: 10.15537/smj.2015.7.11833
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and knowledge regarding antimicrobial stewardship among clinicians in Jeddah, Saudi Arabia

Abstract: Objectives:To understand the perceptions, attitude, and prescribing practices of clinicians regarding antimicrobial resistance (AMR).Methods:A multidisciplinary cross-sectional study comprising 447 clinicians of university, public, and private hospitals of Jeddah, Saudi Arabia was carried out from August to October 2014 using a self-administered questionnaire.Results:Interestingly, 33% of the general physicians yielded to patient/parent’s demand for the choice of antimicrobials (AMs) as compared with only 13.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…Unfortunately, nearly all the respondents in the current study do not know that therapeutic monitoring of antibiotic, study of antibiotics and improved hygiene were also strategies of ABS (Abbo et al, 2013;Roca et al, 2015). The major key factor in the repression of ABR is reduction of disproportionate antibiotic utilization and this could be accomplished to a great extent by modification of prescribing manners of the clinicians/veterinarians (Dryden et al, 2011;Al-Harthi et al, 2013;Al-Harthi et al, 2015). Reduction in antibiotic use in veterinary settings could be achieved by improved personal hygiene by the veterinarians, animal handlers / caretakers and improved environmental sanitation (biosecurity) in the farm (Coyne et al, 2016: Rhouma et al, 2016.…”
Section: Discussionmentioning
confidence: 89%
“…Unfortunately, nearly all the respondents in the current study do not know that therapeutic monitoring of antibiotic, study of antibiotics and improved hygiene were also strategies of ABS (Abbo et al, 2013;Roca et al, 2015). The major key factor in the repression of ABR is reduction of disproportionate antibiotic utilization and this could be accomplished to a great extent by modification of prescribing manners of the clinicians/veterinarians (Dryden et al, 2011;Al-Harthi et al, 2013;Al-Harthi et al, 2015). Reduction in antibiotic use in veterinary settings could be achieved by improved personal hygiene by the veterinarians, animal handlers / caretakers and improved environmental sanitation (biosecurity) in the farm (Coyne et al, 2016: Rhouma et al, 2016.…”
Section: Discussionmentioning
confidence: 89%
“… 39 Data from Saudi Arabia showed that despite good levels of awareness among physicians regarding MDR and the existence of local and national antimicrobial prescribing guidelines, a great proportion of them stated that they do not always comply with these guidelines. 40 , 41 Fear for patient’s prognosis, in addition to complacent prescribing, have been found to be the most significant risk factors of antibiotic misprescription. 41 - 43 A communication from the National Institute for Health and Care Excellence (NICE) in the UK reported that 9 out of 10 general practitioners feel pressured to prescribe antibiotics and almost 100% of patients can get an antibiotic prescription on request.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that Saudi diabetic patients were significantly more likely to carry carbapenem-resistant isolates of this species (Alsultan et al 2013). It has now become crucial to deal with MDR and this is possible by first being aware of the perils involved and then formulating and complying with appropriate guidelines (Baadani et al, 2015;Al-Harthi et al, 2015). The present study is an effort to determine the prevalence and antimicrobial susceptibility pattern of Acinetobacter spp.…”
Section: Introductionmentioning
confidence: 99%